Congo-Crimean haemorrhagic fever in Dubai: histopathological studies. Issue 8 (August 1981) - Baskerville, A; Satti, A; Murphy, F A; Simpson, D I
Abstract : Necropsies were carried out on two patients who died of Congo-Crimean haemorrhagic fever (C-CHF) in Dubai. The diagnosis was confirmed by isolation of C-CHF virus from the liver. Histopathological changes included extensive cellular necrosis and haemorrhage in the liver, necrosis and lymphoid depletion in the spleen, congestion and oedema formation in the lungs, and haemorrhage in a number of other organs.